2001
DOI: 10.1080/09687680110075101
|View full text |Cite
|
Sign up to set email alerts
|

Precursor cystatin C in cultured retinal pigment epithelium cells: evidence for processing through the secretory pathway

Abstract: Evidence was recently reported that the cysteine proteinase inhibitor, cystatin C, is highly expressed by cultured human retinal pigment epithelial (RPE) cells. As a step towards understanding possible functions of this protein associated with the RPE, the localization, targetting and trafficking of cystatin C were investigated. Constructs encoding an enhanced variant of green fluorescent protein (EGFP) fused to precursor cystatin C and to mature cystatin C were made and transfected into cultured human RPE cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…All cell lines transfected with pGFP‐PERP construct showed marked plasma membrane‐associated fluorescence, with additional perinuclear localization in the cytoplasm, previously identified as the endoplasmic reticulum (ER)/Golgi apparatus [36, 37], and with no detectable fluorescence signal in the nucleus (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…All cell lines transfected with pGFP‐PERP construct showed marked plasma membrane‐associated fluorescence, with additional perinuclear localization in the cytoplasm, previously identified as the endoplasmic reticulum (ER)/Golgi apparatus [36, 37], and with no detectable fluorescence signal in the nucleus (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the mutations in the presenilin 2 gene that are linked to FAD (PS2 M239I and T122R) alter CysC trafficking in mouse primary neurons and cause reduced CysC secretion (Ghidoni et al, 2007). The primary structure of CysC is indicative of a secreted protein and accordingly, it was demonstrated that most of the CysC is targeted extracellularly via the secretory pathway (Wei et al, 1998; Paraoan et al, 2001). Moreover, it was recently shown that CysC is also secreted in association with exosomes (Ghidoni et al, 2011).…”
Section: Cysc and Alzheimer's Diseasementioning
confidence: 99%
“…Newly synthesized CysC is secreted from all cell types 19–24 , secreted CysC can be internalized into cells via endocytosis 2527 , and uptake of CysC can occur by cells other than the cell producing the protein 2527 , suggesting that in vivo CysC can mediate important communications between cells. In addition to being targeted to the classical secretory pathway, CysC is secreted in association with EVs 28 .…”
Section: Introductionmentioning
confidence: 99%